Inflammatory and cardiovascular diseases biomarkers in chronic hepatitis C virus infection: A review. Issue 3 (30th November 2019) - Babiker, Ahmed; Hassan, Mohamed; Muhammed, Safwan; Taylor, Gregory; Poonia, Bhawna; Shah, Anoop; Bagchi, Shashwatee
Abstract: Hepatitis C virus (HCV) infects 180 million people worldwide and over 4 million people in the United States. HCV infection is a major cause of chronic liver disease and is recognized as a risk factor for clinical cardiovascular disease (CVD). Many studies have shown increased prevalence of cardiac and inflammatory biomarkers in patients with chronic HCV infection (CHC), and though these markers may be used to risk stratify people for cardiac disease in the general population their role in the HCV population is unknown. Patients with CHC have elevated cardiac and inflammatory biomarkers compared to noninfected controls which may play a role in CVD risk stratification. We undertook a systematic review of inflammatory and cardiac biomarkers in people with HCV infection with a focus on the effect of CHC on serum levels of these markers and their utility as predictors of CVD in this population. Medline, EMBASE, and Cochrane databases were searched for relevant articles until June 2019. A total of 2430 results were reviewed with 115 studies included. Our review revealed that HCV infection significantly alters serum levels of markers of inflammation, endothelial function, and cardiac dysfunction prior to HCV treatment, and some of which may change in response to HCV therapy. Current risk stratification tools for development of CVD in the general population may not account for the increased inflammatory markers that appear to be elevated among HCV‐infected patients contributing to increased CVD risk.